Allelopathic Effect of Leaf Extract of Ochlandra travancorica on the Germination of Cicer arietinum: Allelopathic Effect of Leaf Extract of Ochlandra travancorica on the Germination of Cicer arietinum - Nisha, S. A. (International Journal of Pharmaceutical & Biological Archive, 2019)
In the present investigation, aqueous extracts prepared from fresh leaf and dry leaf of Ochlandra travancorica showed inhibitory effects on seed germination in Cicer arietinum (Bengal gram), in different concentrations. The allelopathic effect of the fresh and dry leaf extracts of O. travancorica shows that it decreases the rate of seed germination in C. arietinum with an increase in the concentration of aqueous extracts. The maximum percentage of germination was recorded at control condition and the minimum percentage or no growth was recorded in 10%, 20%, 50%, and 100%. The germination rate at a concentration <10% was taken for biochemical and phytochemical analysis. The biochemical components and some active constituents like the secondary metabolites in the shoot, leaf, and cotyledon were also analyzed. The pigment analysis of the germinated leaves was also undertaken. These results indicate that the inhibitory effect on the germination of seeds may be due to allelopathy and the allelochemicals present in the leaves of this bamboo species.